KEPASTIAN HUKUM PENERBITAN PERSETUJUAN LINGKUNGAN HIDUP DI KOTA SURABAYA - Syafira Indra Rochmana; Bambang Arwanto (Jurnal HUKUM BISNIS, 2022)
Environmental Permit is a license that must be owned by business actors. Therefore, the Surabaya City government issued a regulation regarding environmental permits. However, with the issuance of a new regulation, namely the Job Creation Act and its derivatives, the Surabaya City Mayor contradicts the regulation. Surabaya, namely revoking these regulations and replacing new regulations in accordance with higher regulations in force. Key Words: Environmental Permits, Government Actions, City of Surabaya